Raspberry Pi - Wentk, Richard (Teach yourself visually., 2014)
Full-color, step-by-step guidance for learning to use Raspberry Pi! Raspberry Pi is an inexpensive, single-board computer that serves as an introductory board for students and developing computer professionals. This image-driven, visual guide shows you how the Raspberry Pi can be easily used as a stand-alone computer, a media center, a web server, and much more. Vivid, full-color images bring Raspberry Pi projects to life, while well-illustrated circuit diagrams and step-by-step practical advice cover everything from working with the included software to branching out into typi.